2021
DOI: 10.3390/ijerph18052408
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness Is Associated with Depressive Affect, But Not with Most Other Symptoms of Depression in Community-Dwelling Individuals: A Network Analysis

Abstract: There is a strong relationship between loneliness and depression, but depression is a heterogeneous disorder. We examined the profile of depressive symptoms most strongly related to loneliness. Study participants were 2007 community-dwelling individuals (median age 31 years, 70.4% women) who completed an online survey on loneliness (single-item question: “never”, “sometimes”, “often”), depressive symptoms (Patient Health Questionnaire-9) and demographics. The relationship between loneliness and depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…In both models, women had higher odds of considering themselves lonely and individuals feeling nervous were more likely to feel lonely compared to their counterparts. Similarly to the reported results of von Känel et al (2021) or Wickens et al (2021), our findings show that out of socio-demographic characteristics, being a women and sensitive to adverse health conditions can serve as a risk factor predicting loneliness. In concordance with previous evidence of an association between health-related physical and mental outcomes and loneliness (Savikko et al, 2005, Victor et al, 2005, the current study found that poor health and trouble sleeping was significantly associated with loneliness but lost its significance in the 2021 regression model.…”
Section: Discussionsupporting
confidence: 89%
“…In both models, women had higher odds of considering themselves lonely and individuals feeling nervous were more likely to feel lonely compared to their counterparts. Similarly to the reported results of von Känel et al (2021) or Wickens et al (2021), our findings show that out of socio-demographic characteristics, being a women and sensitive to adverse health conditions can serve as a risk factor predicting loneliness. In concordance with previous evidence of an association between health-related physical and mental outcomes and loneliness (Savikko et al, 2005, Victor et al, 2005, the current study found that poor health and trouble sleeping was significantly associated with loneliness but lost its significance in the 2021 regression model.…”
Section: Discussionsupporting
confidence: 89%
“…Although several German translations of the MBI-GS do exist, none has officially been validated. Nevertheless, the chosen translation has been widely used in previous research (e.g., [ 27 , 28 ] and demonstrated good internal consistency in this study with Cronbach’s alpha of 0.91 for the MBI-GS total score.…”
Section: Methodsmentioning
confidence: 95%
“…Future studies using multi‐item scales could employ structural equation models to allow for latent variable modelling and more precise multigroup analyses 42 . It is noteworthy however that loneliness appears to primarily be associated with depressed affect—the symptom measured in SHARE—and less with other symptoms of depression 43 . We also assessed social network size via the number of trusted confidants.…”
Section: Discussionmentioning
confidence: 99%
“…42 It is noteworthy however that loneliness appears to primarily be associated with depressed affect-the symptom measured in SHARE-and less with other symptoms of depression. 43 We also assessed social network size via the number of trusted confidants. While this operationalisation implies trust and thus a positive, valued relationship, it does not differentiate the closeness of relationships, therefore the interaction of number of confidants and closeness on loneliness and depression is subject to future research.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%